Technique of Remote Sensing and its Importance in Monitoring Valley Floods in Libya - Dr. Ghada Mohammed Ali Ahweedi (Journal of Scientific and Human Dimensions, 2026)
Floods are the most frequent and impactful weather-related disaster in terms of the number of people affected. Therefore, flood mitigation and rapid response are crucial to minimizing human losses. Remote sensing technologies have proven effective in analyzing and monitoring various natural disasters. Using tools such as satellites excellent for mapping the spatial distribution of disaster data over relatively short periods—resources provide accurate, frequent, and near-instantaneous data for vast areas anywhere in the world. Remote sensing can provide a wealth of information on floods and their prediction through various techniques, including image processing, rainfall data analysis, and flood mapping. Despite the increasing number of remote sensing applications, these technologies are underutilized in Libya for flood research and prediction. This study aims to provide a comprehensive review of the literature covering aspects of remote sensing applications for flood management, including flood detection, affected area identification, and damage assessment. The study encompassed both flood monitoring using satellite-derived rainfall data and flood monitoring based on changes in land cover as observed in satellite imagery